O Tribunal do Santo Ofício espanhol: Continuidades e inovações nas práticas processuais (Sécs. XIV-XVI) - Gomes, Daiany Souza Macelai de Oliveira (2009)
Extremely marked by the elements of the previous Inquisition, the Spanish Inquisition arises as a joint of influences and conducts of the first one, but reflects, at the same time, specific elements that differs it from the medieval practice. The subject of the dissertation summarizes itself in the perception of the similarities and differences in the Spanish Inquisition conduct in relation to the medieval one following the analysis of the Inquisitor Manual from Nicolau Eymerich and its analysis by Francisco de La Penã in a comparative methodology. At first sight we show the history context to the production of the Inquisitor Manual and its legal content. Later we will try to take in structural context of the Spanish Inquisition and its specific elements in Peña’s context. Finally we will detach some chances at the Court’s action concerning the Inquisition rituals proceedings based on Peña’s analysis.